2021
DOI: 10.1093/ofid/ofab524
|View full text |Cite
|
Sign up to set email alerts
|

A Multidimensional Cross-Sectional Analysis of Coronavirus Disease 2019 Seroprevalence Among a Police Officer Cohort: The PoliCOV-19 Study

Abstract: Background Protests and police fieldwork provides a high exposure environment for SARS-CoV-2 infections. In this cross-sectional analysis, we investigated the seroprevalence among a police cohort, and sociodemographic, work and health-related factors associated with seropositivity. Methods Study participants were invited for serological testing of SARS-CoV-2 and to complete online questionnaires. Serum neutralization titres t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…The presence or absence of seroconversion between the baseline and 3‐month visit was investigated in 956 paired samples, and between the 3‐ and 6‐month visits in 955 paired samples. The seroprevalences of anti‐NCP antibodies—without adjusting for paired sample results or false positive or false negative results—were 12.9% at baseline, 5 14.4% at the 3‐month visit, and 15.3% at the 6‐month visit (Appendices, Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence or absence of seroconversion between the baseline and 3‐month visit was investigated in 956 paired samples, and between the 3‐ and 6‐month visits in 955 paired samples. The seroprevalences of anti‐NCP antibodies—without adjusting for paired sample results or false positive or false negative results—were 12.9% at baseline, 5 14.4% at the 3‐month visit, and 15.3% at the 6‐month visit (Appendices, Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our cohort, the seroprevalence at the baseline was 12.9% in February 2021, similar to that reported in the general population. 5 The self‐reported compliance with mask‐wearing during working hours was very high. The results suggested that household contacts were the leading transmission venues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations